Efficacy and tolerability of lercanidipine in mild to moderate hypertension among Asians of different ethnic groups - Chia, Y.C. (2009)
Introduction: Calcium channel blockers are well established modalities for the treatment of hypertension. However, in spite of the availability of many efficacious agents, hypertension control continues to be poor. One reason is poor tolerability due to adverse events. Racial differences also exist. Lercanidipine, a third-generation calcium channel blocker, is associated with better tolerability. However, it has not been studied in the Asian population. This study examines its efficacy and tolerability in Asian subjects of different ethnicities. Methods: This was an eight-week open label study of adults with mild to moderate hypertension. Blood pressure (BP), pulse rate, self-administered symptom check and laboratory evaluations were done at baseline. Patients were prescribed 10 mg lercanidipine, with up-titration to 20 mg if BP was not controlled at Week 4. Baseline evaluations were repeated at Week 8. Adverse events were also enumerated. Results: 27 patients (mean age 53.4 +/- 12.1 years) completed the study. The baseline systolic BP (SBP), diastolic BP (DBP) and heart rate was 159 +/- 12.2, 96.6 +/- 7.7 mmHg and 71 +/- 13/min, respectively. Three racial groups were represented. SBP and DBP decreased significantly after four weeks of therapy. A further reduction to 139 +/- 14.3 and 88 +/- 9.8 (p-value is less than 0.0001) was seen in Week 8. The absolute SBP and DBP reduction was 20.5 mmHg (95 percent confidence interval CI 16.5-24.5, p-value is less than 0.0001) and 9.3 mmHg (95 percent CI 6.2-12.5, p-value is less than 0.0001), respectively. All adverse symptoms, except for palpitations, were reduced at the end of the study. Conclusion: Lercanidipine is efficacious and well tolerated in Asians of different ethnicities. Its BP lowering effects and tolerability in Asians appear to be similar to other studies on Caucasians and other calcium channel blockers.